Ekonomi dan Politik Pendekatan Maqasid Syariah - Mifti Ibdalia; Muhammad Albahi (Masyarakat Ekonomi Syariah Bogor, 2025)
Economics and politics are two important aspects that shape the structure of human social life. In Islam, these two fields are not only seen as a means to achieve material prosperity, but also as a means to achieve prosperity in this world and the hereafter. For this reason, the approach used in economics and politics must be in line with sharia principles, which are based on larger goals, namely maqasid sharia. Maqasid Syariah, which literally means